THE INFORMATION CONTENT OF QUARTERLY FINANCIAL REPORTS:EVIDENCE FROM CHINA - Lin, Zhiguo (My University, 2009)
This study investigates the information content of listed companies’ quarterly financial reports in China. The purpose of the study is two-fold. First, the study investigates whether the quarterly financial reports of listed companies in China have information content. Second, using the empirical results, the study further to define which market efficiency that China’s stock market belongs to. The sample includes 300 listed companies in Shanghai and Shenzhen Stock Exchange. The data consist of daily stock prices of the 300 listed companies in event window, daily stock indices in Shanghai and Shenzhen, quarterly EPS and ROE disclosed in the financial reports. The data period is from 2002 to 2008. The empirical findings indicate that: 1) The abnormal returns and cumulative average abnormal returns before and after the announcement of quarterly financial report change obviously, which mean that the quarterly earning reports have information content in Chinese A-share market. 2) By analyzing unexpected earnings which classify as favorable news and unfavorable news, the empirical results indicates that market may react to different accounting earnings information separately; meanwhile, the market’s reaction to unfavorable news is stronger than favorable news. 3) At the annual inspection, earnings response coefficients enhances significantly, this proves that investors in A-share market pay more and more attention to accounting earning of listed companies. 4) The empirical results tend to indicate that the Chinese A-share market is basically under the state of semi-strong efficiency, or at least, under an effective process from weak efficiency to semi-strong form efficiency.
Keywords: Information content; Effective market; Listed companies; Quarterly report; fi=Finance and Accounting|; fi=Master's Degree Programme in Finance|